K-Ar age determinations of the late Tertiary and Quaternary Andean volcanic rocks, southern Peru - Kaneoka, Ichiro (1984)
K-Ar ages were determined on 30 Andean volcanic rocks from southern Peru, most of which were considered to belong to the Barroso Group of Quaternary in age. The results have revealed, however, that their ages range from late Miocene to recent (7.2 to less than 0.03 Ma). This indicates that the Barroso Group samples might include much wider age ranges than had been assigned. Relatively young volcanic activity of late Quaternary is apparently restricted in the northwestern part including the vicinity of Arequipa in the investigated area. The main volcanic activity in the southwestern part seem to have almost ended by early Pleistocene. The shoshonitic rocks which are located around the Puno area probably extruded about 6Ma ago in a relatively short period of less than a few hundred thousand years.